Antitumor Effect of Laminaria japonica Polysaccharide WLP5 in MCF-7 Breast Cancer Cell-Bearing Mice - CAO Mingyuan, LI Ying, QI Guohong, YANG Zhiping, HUANG Dechun, CHEN Guitang (Shipin Kexue, 2023)
In order to investigate the effect of Laminaria japonica polysaccharide WLP5, obtained by hot water extraction, on immune function and the growth of tumor in MCF-7 breast cancer cell-bearing mice, MCF-7 tumor-bearing nude mice were randomly divided into four groups (n = 10 each): model, positive control (doxorubicin hydrochloride, 0.4 μg/kg mb), low-dose (50 μg/kg mb) and high-dose (200 μg/kg mb) WLP5. All mice were treated by intragastric administration every other day for 50 days. The long and short diameters of tumor, tumor volume, tumor inhibition rate, hematological indicators and the concentrations of serum cytokines including interleukin-2 (IL-2), IL-6, transforming growth factor-β (TGF-β) and tumor necrosis factor-α (TNF-α) were determined and pathological changes of liver and tumor sections from mice in each group were observed. The results showed that the long diameter, short diameter and volume of tumor in the low- and high-dose WLP5 groups significantly decreased in comparison to the model group (P < 0.05 or P < 0.01), and the tumor inhibition rates were 36.5% and 48.9%, respectively. Compared with the model group, monocyte percentage significantly decreased (P < 0.05) and mean platelet volume significantly increased in the high-dose group (P < 0.05), but no significant differences were found in any other hematological indicators. Moreover, WLP5 at low and high doses significantly increased the release of IL-2 and IL-6 (P < 0.05 or P < 0.01). The results of pathological sections suggested that the liver tissue of mice in the high-dose group was complete, while the tumor cells showed large areas of necrosis and the nuclei disappeared, indicating that WLP5 has strong antitumor effect in vivo without obvious toxicity to normal cells or tissues. The antitumor activity of WLP5 is related to the regulation of immune function.